Nodosin Exerts an Anti-Colorectal Cancer Effect by Inhibiting Proliferation and Triggering Complex Cell Death in Vitro and in Vivo - Fan, Huixia; Hao, Xiaopeng; Gao, Yuan; Yang, Jian; Liu, Aojun; Su, Yarui; Xia, Yong (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is one of the most common digestive system cancer in the world. Its incidence and mortality are increasing annually. Presently, CRC lacks long-term effective treatment methods and drugs. Therefore, finding new treatment methods and drugs is of great significance for CRC treatment. Compounds derived from natural plants have been widely used in tumor research and treatment because of their good antitumor activity these years. This study found that nodosin, a diterpenoid extracted from the medicinal plant Rabdosia serra (Maxim.) Hara, inhibited the growth of CRC cells SW480, HT-29 and LoVo in a dose- and time-dependent manner, with inhibitory concentrations (IC50) of 7.4 μM, 7.7 μM and 6.6 μM respectively. We selected highly metastatic and poorly differentiated SW480 cells for further studies. We found that nodosin could inhibit cell proliferation by inhibiting DNA synthesis and induce cell death by inducing oxidative stress, apoptosis and autophagy in cells. Through in vitro assays combined with transcriptomic analysis, it was found that nodosin could downregulate tribbles pseudokinase 3 and upregulate oxidative stress-induced growth inhibitor 1 to induce oxidative stress in cells; nodosin-induced reactive oxygen species were able to upregulate the expression of heme oxygenase 1 to induce apoptosis and the expression of cathepsin L and light chain-3 to induce autophagy. In vivo, we found that nodosin inhibited tumor growth and induced cells to undergo apoptosis and autophagy without significant toxic effects. In conclusion, our findings suggest that nodosin exerts anti-CRC effects mainly through its ability to induce apoptosis and autophagy in vitro and in vivo. Therefore, our study contributes to the development of nodosin-based potential CRC therapeutic drugs.